Reseñas - Hinojosa, Olga; González, Lara; Classen, Albrecht; Juan-Fadrique Fernández; Eva Parra-Membrives; Rosa Marta Gómez Pato (Futhark. Revista de Investigación y Cultura, 2021)
En este apartado aparecerán reseñas de diversos textos